Analysis of Prevention Measures on Post Gastritisine - Sinaga, Erra Meilani; Marniati, Marniati; Putri, Enda Silvia (Universitas Teuku Umar, 2023)
Lifestyle is characterized by behaviour patterns that can impact individual health, especially unhealthy ones such as smoking, stress, and unhealthy eating patterns that can lead to various digestive disorders. This study aimed to analyze prevention efforts against the recurrence of post-gastritis sufferers in the Kuala sub-district, Nagan Raya Regency. This qualitative research method analyzes and describes phenomena or objects of research through social activities, attitudes, and perceptions of people individually or in groups. The informants in this study were eight people, with details of 1 Head of the Public Health Center, 1 Head of Gastritis, 1 Doctor of the Public Health Center, and five patients with post-gastritis in Kuala sub-district Nagan Raya Regency in October 2022. Results of this study indicate that the diet of post-gastritis sufferers is irregular, and they also consume spicy food unnaturally; post-gastritis sufferers are also unable to manage the stress they experience, so they have the habit of drinking coffee with inappropriate doses, and gastritis is supported by the behaviour of post-gastritis sufferers who have a smoking habit that is difficult to change. This study concludes that the lifestyle of post-gastritis sufferers who are not good has a significant influence on the recurrence of gastritis.